Slow ethics and the art of care - Gallagher, Ann (Emerald points., 2020)
The path to good care-giving can be challenging, particularly where practices are characterised by crisis, moral panic and cultural complexity. How can we respond ethically when there is pressure to meet targets, work faster and implement quick, short-term fixes? This book offers a solution in the form of slow ethics.